Inovasi Pembelajaran: Meningkatkan Literasi Sains Siswa Sekolah Dasar melalui Model dan Media yang Menarik - Nurfadilah, Aisah; Cahyaningsih, Ujiati (Universitas Pahlawan Tuanku Tambusai, 2024)
Having scientific literacy skills is a must for every individual, especially elementary school students, so that they can explore, use, and evaluate scientific information to produce the right decisions in everyday life. This study aims to determine the models and media that are most widely used in improving scientific literacy skills in science learning in elementary schools. The technique used in this study is the Systematic Literature Review (SLR), where the study was conducted by reviewing several articles related to the models and media used in improving scientific literacy skills in science learning in elementary schools with a span of 2018-2023. Literature studies were obtained from search results in databases such as Google Scholar, Garuda, Sinta, DOAJ, ERIC, and Taylor and France. Based on the results of data analysis from 25 articles, the results of the data analysis showed that the models and media that were most widely used to improve scientific literacy skills in science learning in elementary schools were the Problem Based Learning (PBL) model and video learning media. Thus, the Problem Based Learning (PBL) model and video media have proven effective in improving scientific literacy skills in science learning in elementary schools.